Morphine and buprenorphine do not alter leukocyte cytokine production capacity, early apoptosis, or neutrophil phagocytic function in healthy dogs. (April 2015) - Monibi, Farrah A.; Dodam, John R.; Axiak-Bechtel, Sandra M.; Amorim, Juliana; Zhang, Yan; Tsuruta, Kaoru; Mann, F.A.; DeClue, Amy E.
Highlights: We evaluated the effects of opioids on innate immune function in healthy dogs. Opioids do not significantly affect leukocyte stimulated cytokine production. Opioids do not significantly affect early leukocyte apoptosis or phagocytic function. There is a potential association between hospital stress and cytokine production. Dogs could be less sensitive to immunomodulatory effects of acute opioid treatment. Abstract: Opioids have immunomodulatory properties in many species, but there is little information pertaining to these properties in dogs. Our objective was to compare the in vivo effects of morphine, buprenorphine, and control solution on innate immune system function and apoptosis in healthy dogs. Six adult dogs received a 24-hour infusion of morphine, buprenorphine, or control solution (saline) in a randomized, controlled, crossover block design. Leukocyte apoptosis, phagocytosis, and oxidative burst were evaluated using flow cytometry. Lipopolysaccharide, lipoteichoic acid, and peptidoglycan-stimulated leukocyte production of tumor necrosis factor (TNF)-α, interleukin (IL)-6, and IL-10 were determined using canine specific multiplex assays. No significant treatment effects were detected among groups. These data suggest that healthy dogs could be less sensitive to the immunomodulatory effects of acute opioid administration compared with other species. Larger investigations in healthy and immunologically challenged dogs are recommended prior to application of these results in clinical patients.